WOMANPOWER: A LOOK AT A WOMEN’S ORGANIZATION AMONG GRADUATE STUDENTS IN EDUCATIONAL ADMINISTRATION - Weinrub-Lusthaus, Evelyn; Schweber-Koren, Claudine (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1975)
As women graduate students studying to become educational administrators, we clearly knew we were in the minority. When we looked about, we realized that we were only eleven women among over two hundred part-time and full-time students in our Department of Educational Administration. When we looked a bit more, we learned that the proportion of women in our department was illustrative of the educational administration field as a whole: nationally in 1973 only two percent of all professors of educational administration were women, and only twenty-six percent of public school administrators were women. Sex-segregation in the field of education was pervasive, with women highly concentrated in teaching and men highly concentrated in administration.